2015
DOI: 10.1111/1469-8676.12101
|View full text |Cite
|
Sign up to set email alerts
|

The normativity of numbers in practice: technologies of counting, accounting and auditing in Malawi's civil service reform

Abstract: Contemporary technologies of governing employed in international development rely on the normativity of numbers, and their use of numbers and collection, as conditions for financial support by international financial institutions. This article examines how the normativity of numbers worked in practice during the implementation of civil service reform in Malawi. It reveals a contradiction between the lofty rhetoric of greater efficiency and transparency achieved through the introduction of new technologies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…(Gong, 2009a(Gong, , 2009bMathur, 2012;Smart, 2018;Wilcock, 2019). Cases of the latter are health-care providers in the USA (Koreff et al, 2021), the Brazilian Regional Courts of Accounts (Lino et al, 2021), the City of Montréal (Courtois and Gendron, 2017), local government in Australia (Pilcher, 2014), higher education (Shore, 2018), police services (Chan, 1999) or civil servants' policies (Anders, 2015).…”
Section: Preliminary Analysis Of Resultsmentioning
confidence: 99%
“…(Gong, 2009a(Gong, , 2009bMathur, 2012;Smart, 2018;Wilcock, 2019). Cases of the latter are health-care providers in the USA (Koreff et al, 2021), the Brazilian Regional Courts of Accounts (Lino et al, 2021), the City of Montréal (Courtois and Gendron, 2017), local government in Australia (Pilcher, 2014), higher education (Shore, 2018), police services (Chan, 1999) or civil servants' policies (Anders, 2015).…”
Section: Preliminary Analysis Of Resultsmentioning
confidence: 99%
“…The integrity of digital systems is further eroded by regular security breaches; and the centralisation of biometric or identity data in national repositories increases the reward for external hackers, whilst creating almost 'infinite' opportunities for internal official misuse of personal data (Breckenridge, 2005, p.281). Whilst digital fraud in public systems is also prevalent in most other countries (Anders, 2015;Busch & Henriksen, 2018), African states tend to lack the skills needed to effectively counter these threats (Barata & Cain, 2001).…”
Section: Working Practicesmentioning
confidence: 99%
“…Similarly, Anders's study (2015) revealed that the Malawi Government has emphasised the aspects of efficiency and transparency in the public sector through the implementation of technologies ("process" -Figure 3). In fact, the implementation of clean government in Africa, in general, has been hindered by bureaucratic practices and corruption (Anders, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%